2005
DOI: 10.1016/j.virol.2005.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of RNA structures present at the 3′UTR of dengue virus on translation, RNA synthesis, and viral replication

Abstract: We have developed a dengue virus replicon system that can be used to discriminate between translation and RNA replication. Using this system, we analyzed the functional role of well-defined RNA elements present at the 3'UTR of dengue virus in mammalian and mosquito cells. Our results show that deletion of individual domains of the 3'UTR did not significantly affect translation of the input RNA but seriously compromised or abolished RNA synthesis. We demonstrated that complementarity between sequences present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
284
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(304 citation statements)
references
References 37 publications
15
284
1
4
Order By: Relevance
“…The DENV 3'-UTR is believed to play a key role in the regulation of viral replication by virtue of controlling RNA synthesis [35]. Both viral and cellular factors are known to bind to the 3'-UTR, and these interactions appear to regulate the efficiency of RNA replication [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DENV 3'-UTR is believed to play a key role in the regulation of viral replication by virtue of controlling RNA synthesis [35]. Both viral and cellular factors are known to bind to the 3'-UTR, and these interactions appear to regulate the efficiency of RNA replication [34].…”
Section: Discussionmentioning
confidence: 99%
“…Both viral and cellular factors are known to bind to the 3'-UTR, and these interactions appear to regulate the efficiency of RNA replication [34]. There is some evidence suggesting that the attenuating effects of deletion mutations in the 3'-UTR are mediated by a disruption in secondary structure that results in a decrease in the efficiency of RNA replication [35]. Studies by Men et al first characterized a panel of deletion mutations of varying length in the 3'-UTR of DENV-4 [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with the other positive strand RNA viruses, the 5′NCR and 3′NCR of DENV are predicted to form secondary RNA structures and cyclization which interact with cellular and viral proteins for viral protein translation (Ali and Siddiqui, 1995) and RNA genome replication (Guesdon et al, 2001;Kuhn et al, 2002). Sequences of 5′NCR together with capsid protein gene and 3′NCR are required to structurally interact during virus replication (Alvarez et al, 2005;You et al, 2001). The functional significance of dengue 5′NCR is demonstrated by the restricted growth of DENV-4 deletion mutants (Cahour et al, 1995), attenuation effect of the DENV-2 PDK-53 vaccine candidate (Butrapet et al, 2000), and reduced virus replication of DENV-2 5′NCR mutants (Leardkamolkarn et al, 2010;Sirigulpanit et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…DENV-2 New Guinea C replicons containing GFP or luciferase reporter stabilized in BHK-21 cells were established for antiviral screening and siRNA testing (Ng et al, 2007). DENV-2 16681 replicon containing luciferase reporter was created and used to study 3′NCR structure and an anti-viral compound targeting the 3′NCR (Alvarez et al, 2005;Holden et al, 2006). In this study, we reported various strategies in constructing DENV-2 replicons with GFP reporter that provided a convenient and fast system to investigate the effects of 5′NCR mutations in viral replication.…”
Section: Introductionmentioning
confidence: 99%